Acute prolonged motor aura resembling ischemic stroke after COVID − 19 vaccination (CoronaVac): the first case report - Wanakorn Rattanawong; Wasan Akaratanawat; Supatporn Tepmongkol; Aurauma Chutinet; Jarturon Tantivatana; Nijasri C. Suwanwela (The Journal of Headache and Pain, 2021)
Abstract Background We report the first case of a patient who suffered transient focal neurological deficit mimicking stroke following CoronaVac vaccination. However, instead of an ischemic stroke, motor aura was suspected. Case presentations A 24 year-old Thai female presented with left hemiparesis fifteen minutes after receiving CoronaVac. She also had numbness of her left arm and legs, flashing lights, and headaches. On physical examination, her BMI was 32.8. Her vital signs were normal. She had moderate left hemiparesis (MRC grade III), numbness on her left face, arms, and legs. Her weakness continued for 5 days. A brain CT scan was done showing no evidence of acute infarction. Acute treatment with aspirin was given. MRI in conjunction with MRA was performed in which no restricted diffusion was seen. A SPECT was performed to evaluate the function of the brain showing significant hypoperfusion of the right hemisphere. The patient gradually improved and was discharged. Discussions In this study, we present the first case of stroke mimic after CoronaVac vaccination. After negative imaging studies had been performed repeatedly, we reach a conclusion that stroke is unlikely to be the cause. Presumably, this phenomenon could possibly have abnormal functional imaging study. Therefore, we believed that it might be due to cortical spreading depression, like migraine aura, which we had conducted a literature review.
Keywords: Migraine and Headache Studies; Retinal and Optic Conditions; Trigeminal Neuralgia and Treatments